2016
DOI: 10.1051/fruits/2016019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carboxymethyl cellulose coating enriched with clove oil on postharvest quality of ‘Xinyu’ mandarin oranges

Abstract: -Introduction. Attempts to exploit natural preservatives to control postharvest diseases as an alternative technology to synthetic fungicides in citrus fruit have been drawing much attention. Materials and methods. The combined effects of carboxymethyl cellulose (CMC) coating and/or clove oil on the qualitative properties of cold-stored 'Xinyu' mandarin oranges stored at 5• C for 120 days were investigated. Results and discussion. The results showed that the addition of clove oil as an antifungal component to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
4
19
0
Order By: Relevance
“…It is shown by us, that CH-HFE and 1.5% chitosan coatings result in a beneficial semi-permeable film surrounding the fruit, modifying the internal atmosphere by elevating CO 2 and/or reducing O 2 , and delaying the degradation rate of nutritional components in navel orange fruits during the mid-later storage period. Our results are in accordance with those of Chen et al [23] and Shah et al [35], where a slow decline in TSS, TA, and VC was recorded in citrus fruits treated with CMC composite coatings. However, other studies have demonstrated that the levels of total soluble solids and acidity, and flavor preferences in "Navel" oranges and "Star Ruby" grapefruits treated with CMC/chitosan bilayer coating, were the same as in the uncoated fruits [48].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is shown by us, that CH-HFE and 1.5% chitosan coatings result in a beneficial semi-permeable film surrounding the fruit, modifying the internal atmosphere by elevating CO 2 and/or reducing O 2 , and delaying the degradation rate of nutritional components in navel orange fruits during the mid-later storage period. Our results are in accordance with those of Chen et al [23] and Shah et al [35], where a slow decline in TSS, TA, and VC was recorded in citrus fruits treated with CMC composite coatings. However, other studies have demonstrated that the levels of total soluble solids and acidity, and flavor preferences in "Navel" oranges and "Star Ruby" grapefruits treated with CMC/chitosan bilayer coating, were the same as in the uncoated fruits [48].…”
Section: Discussionsupporting
confidence: 93%
“…In our research, the incorporation of HFE into 1.5% chitosan coating formulation resulted in a significantly lower respiration rate than 1.5% chitosan coating alone, and uncoated fruits, during the whole storage. Similarly, the respiration rate of citrus fruits coated with CMC edible coatings containing clove oil, Impatiens balsamina L. extract, and silver nanoparticles, has been shown to decrease, compared to uncoated fruits [23,35,52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these phytopathogenic fungi, A. citri showed the least susceptibility to P7G with the highest MIC and MFC value (0.8 g/L). These results are in line with our previous study of clove essential oil (CEO) [35], and indicating that the in vitro antifungal efficiency of CEO may be similar and better than traditional citrus preservatives, with the values of MIC against P. italicum, P. digitatum, G. citri-aurantii, and A. citri ranging from 0.2 to 1.0 mL/L. Peng et al [36] also reported that pinocembrin had potent antifungal activity against P. italicum, with MIC of 0.4 g/L.…”
Section: P7g Displays Potential Used As Antifungal Agent In Citrus Phsupporting
confidence: 93%
“…However, to the best of our knowledge, there is no report on the antifungal activities of Ramulus cinnamomi . Our previous studies have extracted, isolated, and identified some antifungal compounds from the selected antifungal medicinal plants [ 9 , 10 ], which showed good postharvest diseases resistance and maintenance of fruit qualities [ 11 , 12 ]. In continuation, the purpose of the current study was to elucidate the antifungal compounds of Ramulus cinnamomi (RC) and study its antifungal mechanism based on the 1 H-NMR based metabolomics analysis.…”
Section: Introductionmentioning
confidence: 99%